JMASM39: Algorithm for combining robust and bootstrap in multiple linear model regression - Wan Ahmad, Wan Muhamad Amir; Ghazali, Puspa Liza; Mohd Ibrahim, Mohamad Shafiq; Aleng, Azlida; A. Rahim, Hanafi; Abdullah, Zailani (Journal of Modern Applied Statistical Methods Inc, 2016)
The aim of bootstrapping is to approximate the sampling distribution of some estimator.An algorithm for combining method is given in SAS, along with applications and visualizations.